On Kulich - Coe, Sophie (Petits Propos Culinaires, 2024)
This article was inspired by J. Peter Maher’s notes in PPC 9 on the etymology and shape of the ’baba’. The kulich, a Russian Easter speciality, and the baba have many points of resemblance.